Innovation in the Context of the Modern Education Model - Riezanova, Natalia (The University of Rzeszów Publishing House, 2023)
The phenomenon of innovation and its significance for the modern model of education are subjected to scientific reflection, the semantic transformation of the concept of “innovation” and its modern understanding are analysed. It is noted that “innovation” is closely related to such categories as “new”, “discovery”, “creativity”, and the process of innovation is a challenge to the needs of society. The article defines the content of innovation as a form of objectification of the new, which is assigned the status of a factor of social development, analyses the conditions for successful implementation of innovations and the formation of innovative thinking as a necessary component of modern education. The innovative orientation of thinking is analysed through the prism of social and pedagogical innovation processes and is considered as a property of a modern personality. It is innovative thinking that ensures the success of innovative activities, overcoming stereotypes, openness to learning new things and active use of new, non-standard ways of solving complex problems. As part of the learning process, innovative thinking is carried out at the cognitive and instrumental levels and enables the emergence of an innovative personality as a special quality of a person in the modern world.
Keywords: innovation; innovative culture of personality; innovative education; innovative personality; innovative thinking; innovative skills